O nascimento da moral: uma leitura crítica da teoria do desenvolvimento moral de Piaget - Baggio, Bruno Rolim (2019)
The present work consists of a critical reading of the moral theory of Jean Piaget, presented in The Moral Judgment in the Child (1932), a work of great influence in the field of moral psychology. At first, we will try to situate the piagetian theses on morality within the context of the evolution of the author's own thought. As we have tried to demonstrate, Moral Judgment in the Child was published in the initial phase of Piaget's theoretical production and thus precedes some of the author's main contributions in the field of developmental psychology, especially the publication of The Birth of Intelligence in the Child (1936 ), a work in which the author points out the importance of sensory-motor processes, still in the first two years of life, to understand the genesis of logical and conceptual thinking. From this context, it was possible to identify a gap in the moral theses of the author, exactly in relation to the sensorimotor processes that would be the basis of the development of later moral forms such as heteronomy and autonomy. In a second moment, we try to discuss some of Piaget's notes on affective development, which shed new light on the genesis of morality. In The Formation of the Symbol in the Child and the Relations Between Intelligence and Affectivity (1954), the author returned to the theme of morality, but this time accommodating his moral theory to his description of the process of structuring the sensory motor. In these works, the author clarifies some important aspects of affective schematization and points them as a starting point for moral development. Piaget also presents a broader definition of morality, conceiving it as an operative structure of "conduct relating to people." Finally, we address Piaget's effort to integrate contributions from psychoanalysis, especially when he seeks to describe the affective development and dynamics of early interpersonal relationships. We also present some ideas of the pediatrician and English psychoanalyst Donald Wood Winnicott on the genesis of moral development that we consider important for the understanding of a sensorimotor morality (Concern). In addition to being in line with Piaget's description of the early years, Winnicott's descriptions can elucidate a few points not discussed by the Swiss author and contribute to a theoretical renewal consistent with the evolution of his thinking.